Smart cities for whom? Intersectionality and women`s safety perception and violence experience - Macaya, Javiera Fernanda Medina (2023)
This thesis aims to understand how intersectionality shapes women’s experiences in smart cities and analyses how technologies affect such experiences. This qualitative research was conducted based on semi-structured interviews with diverse women. The fieldwork provided information about women’s understanding of smart cities, technologies' role, safety perception and experiences of violence. Besides the critical-interpretive epistemological positioning, a phenomenological approach is used to understand these phenomena, and a deductive and inductive coding process was undertaken in the data analysis. Based on the perspectives of women from the Global South, the research highlights the need to consider intersectionality in designing, implementing, monitoring, and evaluating smart city initiatives. The intersectional approach considers the embeddedness of power, privilege, differentiation, and systems of domination in urban spaces and technologies. Therefore, considering the diversity of shapes and effects, that approach helps comprehend the inequalities in smart cities. The thesis advances some contributions. Using intersectional lenses contributes to the smart city field. It enables the designing of smart city plans and addressing contextual inequalities resulting from differentiation processes and systems of domination in society. The research contributes to understanding women’s perspectives and experiences in the city and technology’s roles. Specifically, it brings Global South perspectives to address these themes, showing how some experiences are particular to our context and, when similar, provide nuances and colours from here. The thesis also contributes to understanding women’s experiences of violence in urban and public spaces. The research shed light on the relevance of analyses focused on understanding the differentiation processes and systems of oppression in violence (especially regarding sexual violence). More nuances about other types of violence also inform which elements should be contemplated in the solutions’ design. Lastly, it shows women’s low expectations about technologies to prevent crimes, particularly those related to sexual violence and their expectations of using them to promote a better reception and support for victims.